2008
DOI: 10.1074/jbc.m709774200
|View full text |Cite
|
Sign up to set email alerts
|

Altered Heparan Sulfate Structure in Mice with Deleted NDST3 Gene Function

Abstract: We report the generation and analysis of mutant mice bearing a targeted disruption of the heparan sulfate (HS)-modifying enzyme GlcNAc N-deacetylase/N-sulfotransferase 3 (NDST3). NDST3؊/؊ mice develop normally, are fertile, and show only subtle hematological and behavioral abnormalities in agreement with only moderate HS undersulfation. Compound mutant mice made deficient in NDST2;NDST3 activities also develop normally, showing that both isoforms are not essential for development. In contrast, NDST1؊/؊ ;NDST3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
51
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(53 citation statements)
references
References 33 publications
1
51
1
Order By: Relevance
“…These data are in correspondence with previous studies reporting a higher level of NDST2 relative to NDST1 in mast cells (16), lymphoid tissues, e.g. thymus and spleen, and whole blood leukocytes (14,47), thus indicating that high expression of NDST2 may be a common feature of cells from the hematopoietic line- ages. Although epithelial cells produce high level of HS by comparison with T lymphocytes and monocytes/macrophages, they are devoid of any high affinity binding sites for CyPB.…”
Section: Discussionsupporting
confidence: 81%
“…These data are in correspondence with previous studies reporting a higher level of NDST2 relative to NDST1 in mast cells (16), lymphoid tissues, e.g. thymus and spleen, and whole blood leukocytes (14,47), thus indicating that high expression of NDST2 may be a common feature of cells from the hematopoietic line- ages. Although epithelial cells produce high level of HS by comparison with T lymphocytes and monocytes/macrophages, they are devoid of any high affinity binding sites for CyPB.…”
Section: Discussionsupporting
confidence: 81%
“…This is quite important for the functional analysis of glycosaminoglycan sulfotransferases, because glycosaminoglycans are sulfated by many sulfotransferases that may have overlapping functions. In fact, many of the mutant animals with deleted heparan sulfate sulfotransferase genes displayed unexpectedly mild phenotypes, which might be explained by the compensatory increase in sulfation at other positions in heparan sulfate (37)(38)(39). In this study, we found that knockdown of UST specifically down-regulated the expression of 2-O-sulfated B and D units in the COS-7 cells without a change in the amount of E unit (Fig.…”
Section: Discussionmentioning
confidence: 48%
“…Hence, NDST activity is a key to the sulfation of heparin, and we therefore chose to study the expression of NDSTs in relation to CTMC-like BMMC maturation. Although four different isoforms of NDSTs (NDST-1-4) have been identified, NDST-1 and NDST-2 appear to be predominant in adult tissue (29). NDST-1 expression was detected already in the early stage (day 0) bone marrow cells, but the level of expression did not increase throughout the process of MC maturation (Fig.…”
Section: Effect Of MC Maturation On Sg Core Protein and Cs/heparin Sumentioning
confidence: 99%